Does reduction mammoplasty improve neck pain and quality of life? Verbessern brustverkleinernde Operationen Nackenschmerzen und die Lebensqualität? - Bragina, Liudmilla; Koehl, Philipp; Dietrich, Maria; Schuh, Alexander (Schmerz, 2022)
Introduction and objective: Macromastia often leads to physical complaints involving pain in the shoulder/neck area. In Germany, there are virtually no reliable data on the effects of breast reduction surgery with regard to neck and spine complaints. Therefore, the authors carried out a retrospective study to investigate the effect of breast-reducing surgery on neck pain and quality of life. Methods: Between January 1, 2014 and December 31, 2019, 107 breast reductions were performed for macromastia. Medical records and OP reports were evaluated, and the indication for breast reduction documented. Pain was recorded preoperatively on a visual analog scale (VAS). Pretreatments and perioperative complications were also documented and evaluated. All patients were sent a questionnaire, which determined whether the objective of the operation had been achieved, how satisfied the patients were with the result of the operation, and how severe the current pain (VAS) was. The EQ-5D 3L health questionnaire was used to assess quality of life, and the Neck-Disability Index was used to assess neck complaints. Statistical analysis was carried out using the Wilcoxon test. Results: After an average of 56.5 months (min: 18, max: 90), 76/107 (71%) patients could be re-examined. There were 15 complications. Pain improved from an average of 7.2 preoperatively (min: 0, max: 10) to an average of 1.6 postoperatively (min: 0, max: 4; p < 0.001). The Neck-Disability Index improved from an average of 43.8% (Min: 0, Max: 82) to an average of 10.8% (Min: 0, Max: 52) postoperatively (p < 0.001). In all, 71/76 (93%) of the examined patients were very satisfied or satisfied with the result of the operation. Discussion and conclusion: With this study, the authors were able to show that there are often several reasons why breast reduction surgery is performed in patients with macromastia. A high patient satisfaction rate can be achieved and orthopedic clinical complaints associated with macromastia can be treated with a very high success rate.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Mamma reduction; Mammahypertrophia; Neck-Disability-Index; Pain; Therapy